A Modified Group Chain Sampling Plans for Lifetimes Following a Rayleigh Distribution - Jamaludin, Aiman Fikri; Zain, Zakiyah; Aziz, Nazrina (Research India Publications, 2016)
In this paper, modified group chain sampling plan is developed for a truncated life test when the lifetime of an item follows Rayleigh distribution.Optimal number of groups and operating characteristic value are obtained by obeying the specified consumer’s risk, test termination time and mean ratio.